Modeling the Effects of Moisture-Related Skin-Support Friction on the Risk for Superficial Pressure Ulcers during Patient Repositioning in Bed - Shaked, Eliav; Gefen, Amit (Frontiers in Bioengineering and Biotechnology, 2013)
Patient repositioning when the skin is moist e.g. due to sweat or urine may cause skin breakdown since wetness increases the skin-support coefficient of friction (COF) and hence also the shear stresses that are generated in the skin when the patient is being moved. This everyday hospital scenario was never studied systematically however. The aim of this study was to simulate such interactions using a biomechanical computational model which is the first of its kind, in order to quantitatively describe the effects of repositioning on the pathomechanics of moisture-related tissue damage. We designed a finite element model to analyze skin stresses under a weight-bearing bony prominence while this region of interest slides frictionally over the support surface, as occurs during repositioning. Our results show, expectedly, that maximal effective stresses in the skin increase as the moisture-contents-related COF between the skin and the mattress rises. Interestingly however, the rise in stresses for a wet interface became more prominent when the skin tissue was stiffer - which represented aging or diabetes. This finding demonstrates how the aged/diabetic skin is more fragile than a young-adult skin when repositioning in a moist environment. The modeling used herein can now be extended to test effects of different moisturizers, creams, lubricants or possibly other interventions at the skin-support interface for testing their potential in protecting the skin from superficial pressure ulcers in a standard, objective and quantitative manner.